Engineering tandem CD33xCD146 CAR CIK (cytokine-induced killer) cells to target the acute myeloid leukemia niche - Alberti, Gaia; Arsuffi, Corinne; Pievani, Alice; Salerno, Domenico; Mantegazza, Francesco; Dazzi, Francesco; Biondi, Andrea; Tettamanti, Sarah; Serafini, Marta (Frontiers in Immunology, 2023)
In acute myeloid leukemia (AML), malignant stem cells hijack the normal bone marrow niche where they are largely protected even from the most innovative current therapeutic approaches. Thus, eradicating these progenitors is the ultimate challenge in the treatment of this disease. Specifically, the development of chimeric antigen receptors (CARs) against distinct mesenchymal stromal cell (MSCs) subpopulations involved in the maintenance of leukemic stem cells within the malignant bone marrow microenvironment could represent a new strategy to improve CAR T-cell therapy efficacy, which is still unsuccessful in AML. As a proof of concept, we generated a novel prototype of Tandem CAR, with one specificity directed against the leukemic cell marker CD33 and the other against the mesenchymal stromal cell marker CD146, demonstrating its capability of simultaneously targeting two different cell types in a 2D co-culture system. Interestingly, we could also observe an in vitro inhibition of CAR T cell functionality mediated by stromal cells, particularly in later effector functions, such as reduction of interferon-gamma and interleukin-2 release and impairedproliferation of the CAR+ effector Cytokine-Induced Killer (CIK) cells. Taken together, these data demonstrate the feasibility of a dual targeting model against two molecules, which are expressed on two different target cells, but also highlight the immunomodulatory effect on CAR CIK cells exerted by stromal cells, confirming that the niche could be an obstacle to the efficacy of CAR T cells. This aspect should be considered in the development of novel CAR T cell approaches directed against the AML bone marrow niche.